Integrating ICT and pedagogy: A transformative model for teaching translation and interpretation - Abd Syakur; Putu Kerti Nitiasih; Rizki Prasetya; I Wayan Eka Mahendra (Journal of Advanced Sciences and Mathematics Education, 2024)
Background: The integration of information and communication technology (ICT) has transformed the educational landscape, including translation and interpretation education. Technological advancements, such as machine translators (MT), have driven the need for innovative teaching methods that enhance both the effectiveness of instruction and students' translation skills.Aim: This study aims to examine the effectiveness of teaching translation and interpretation courses using an ICT-integrated and pedagogical approach.Method: This study employed a pre-experimental design with a one-group pre-test and post-test, involving 26 students selected through random sampling. Data were analyzed using a paired samples t-test to measure significant differences in learning outcomes before and after the implementation of the ICT-based teaching method.Results: The findings indicate that the ICT-integrated and pedagogical approach effectively improves students' translation skills. The paired samples t-test analysis revealed a significant p-value of less than 0.05 (p-value 0.00). Overall, students perceived that the use of Machine Translators (MT) significantly facilitated their translation process, especially when structured practice was provided.Conclusion: The integration of an ICT-based approach in translation instruction has been proven effective in enhancing students' skills. Understanding the concerns and motivations of both students and educators enables curriculum developers to address learning barriers, boost confidence in the use of machine translators, and guide students toward the efficient utilization of technology.